2015
DOI: 10.1016/j.apcatb.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase oxidation of n-decane and PCE by photocatalysis using an annular photoreactor packed with a monolithic catalytic bed coated with P25 and PC500

Abstract: a b s t r a c tPerchloroethylene (PCE) and n-decane are persistently present in the indoor air of several industrial/corporate facilities and households. The present paper reports studies on the photocatalytic oxidation (PCO) of n-decane and PCE using an annular photoreactor equipped with a compound parabolic collector (CPC) and packed with transparent cellulose acetate monolithic structures coated with two commercially available TiO 2 , namely PC500 and P25, under simulated solar light. Such configuration all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 61 publications
1
18
0
3
Order By: Relevance
“…Assadi et al (2012) indicate that the relative humidity (RH) has great and complex effect on the removal of gaseous Trimethylamine (TMA) and isovaleraldehyde (ISOV). The presence of water vapour is beneficial at low concentration due to the formation of •OH radicals which contribute to the increase of degradation; while at higher RH the competitive effect against the active sites becomes predominant (Monteiro et al, 2015); similar experimental result was also observed by Ku et al (2005).…”
Section: Effect Of Relative Humidity On the Degradation Ratesupporting
confidence: 82%
See 1 more Smart Citation
“…Assadi et al (2012) indicate that the relative humidity (RH) has great and complex effect on the removal of gaseous Trimethylamine (TMA) and isovaleraldehyde (ISOV). The presence of water vapour is beneficial at low concentration due to the formation of •OH radicals which contribute to the increase of degradation; while at higher RH the competitive effect against the active sites becomes predominant (Monteiro et al, 2015); similar experimental result was also observed by Ku et al (2005).…”
Section: Effect Of Relative Humidity On the Degradation Ratesupporting
confidence: 82%
“…Zahraa et al (2003) applied an aqueous suspension of TiO 2 for the degradation of atrazine; they used an UV lamp longer than the annular reactor to obtain 80% phase. An annular photoreactor can also be packed with transparent cellulose acetate monolithic structures coated with a catalyst (Monteiro et al, 2015).…”
Section: Annular Photoreactormentioning
confidence: 99%
“…In addition, the produced PC500 film has lower mass in comparison to that of P25 which may be seen as economically advantageous. The superior photocatalytic activity of PC500 films, in comparison to that of P25, was already discussed in our previous works [23] in order to explain the superior activity of PC500 photocatalytic films. Briefly: some authors have ascribed the superior activity of P25, in liquid-phase studies, to the presence of rutile and anatase phases [24][25][26][27].…”
Section: Solar/artificial Uva Pco Of N-decanementioning
confidence: 87%
“…In 441 other words, the high input of PCE molecules into the reactor may prevent the water 442 molecules adsorption on the surface of photocatalytic film. However, in our previous 443 work [38], we reported that the PCO of PCE, in similar operational conditions, over 444 PC500 photocatalytic film is impaired at 40 % RH indicating a possible competition 445 between PCE and water molecules on the surface of the photocatalytic film. As already 446 pointed out by Obee and Brown [29], a PCO process is a result of the combination of 447 pollutant concentration and water content and depends on the relative affinity of 448 photocatalytic film for the pollutant and water molecules and on the mechanism of the 449 hydroxyl radical attack.…”
Section: Ppm) 404mentioning
confidence: 99%